2017
DOI: 10.1111/1365-2745.12827
|View full text |Cite
|
Sign up to set email alerts
|

Cascading effects of changes in land use on the invasion of the walnut Juglans regia in forest ecosystems

Abstract: 1. Plant invasions are affected by many factors that must be favourable in order for invasions to occur. Factors can be grouped into three major categories: propagule pressure, biotic factors and abiotic characteristics; all may be moderated by human activity. However, studies examining all factors simultaneously are rare, and most are limited to a single factor. This hampers our understanding of the mechanisms driving invasions. In recent decades, an alien walnut (Juglans regia) has become invasive in Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
(88 reference statements)
0
25
0
2
Order By: Relevance
“…However, these processes are influenced by the abundance and richness of birds. For example, invasion of the walnut ( Juglans regia ) in Central Europe was due to an increase of bird populations, and the density of walnuts in forest fragments was correlated with bird density (Lenda, Knops, Skórka, Moroń, & Woyciechowski, ). Since, as supported by our study, more birds are found in large forest fragments, large islands have higher probability of seed dispersal by birds (Martínez & García, ), lower asymmetry in ecological networks (Schleuning, Böhning‐Gaese, Dehling, & Burns, ), and consequently, will have more bird‐dispersed plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, these processes are influenced by the abundance and richness of birds. For example, invasion of the walnut ( Juglans regia ) in Central Europe was due to an increase of bird populations, and the density of walnuts in forest fragments was correlated with bird density (Lenda, Knops, Skórka, Moroń, & Woyciechowski, ). Since, as supported by our study, more birds are found in large forest fragments, large islands have higher probability of seed dispersal by birds (Martínez & García, ), lower asymmetry in ecological networks (Schleuning, Böhning‐Gaese, Dehling, & Burns, ), and consequently, will have more bird‐dispersed plants.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the effect was non-linear and the number of tourists had an impact if the number of tourists visiting a given country was high, usually above 20 million. This is also analogous to the invasion process where so-called 'propagule pressure' and continuous colonisations are key triggers of the invasion [50][51][52]. Global travel has increased in overall number, but there has also been a shift in areas visited by travellers, especially in Asia [53].…”
Section: Plos Onementioning
confidence: 99%
“…The probability that seeds will be cached for an extended period rather than eaten depends strongly not only on the functional traits of the seeds (e.g., mass, chemical composition, extended dormancy) but also on the indirect effects of other seed species in the community (Lichti et al, 2017). However, the role of native scatterhoarders in plant invasions is poorly known, even in simple pairwise interactions (Richardson et al, 2000; but see Lenda, Knops, Skórka, Moroń, & Woyciechowski, 2017).…”
Section: Introductionmentioning
confidence: 99%